A guide to CAP reform politics: Issues, positions and dynamics - Valentin Zahrnt (European Centre for International Political Economy (ECIPE), 2011)
CAP reform is the major bone of contention in the negotiations of the next long-term EU budget beyond 2013. This paper reviews the political landscape so as to make it more legible to the public. First, it summarizes the arguments concerning key reform issues: What should be the size of the CAP budget and who should finance agricultural policies? What should happen with direct income support and how to deal with price fluctuations and food security? Which public goods should the CAP pursue and how to promote environmental public goods, in particular? Second, it examines the formal positions as well as the less visible interests and internal conflicts of the main policy actors: DG Agri, the Commission College, the European Parliament, the member states, farmers and landowners, other civil society stakeholders, and academics. Finally, the paper discusses the prospects for the reform process, such as a change in the CAP narrative towards competitiveness and innovation or the increasing influence of financial considerations and broader EU affairs on CAP reform.
Keywords: Q17; Q18; 330; Common Agricultural Policy; political economy; European integration; EU budget; EU-Agrarpolitik; Reform; EU-Haushalt; EU-Staaten